GAYA BAHASA CINTA JIBRAN KHALIL JIBRAN DALAM NOVEL â€œAL-AJNIá¸¤AT AL-MUTAKASSIRATâ€ (Kajian Stilistika) - Fathurohman, Rendi; Syasi, Muhammad; AD, Ahmad Qonit (Hijai - Journal on Arabic Language and Literature, 2019)
This article aims to explain the style that is identified in Jibran Khalil Jibranâ€™s novel â€œal-Ajnihat al-Mutakassiratâ€. The style includes diction, sentence, figurative language and meaning effect based on Ahmad Sayyebâ€™s theory that is clearness, force, beauty, and pressing. The styles used by Jibran includes 1) Diction that is repeating the same sound in makhraj and using synonyms, and 2) The sentence includes mumtaddah, mutaâ€™addidah, murakkabah, and mutasyÄbikah. 3) Figurative language includes figure of thought and figure of speech. The figure of thought includes simile, metaphor, personification, metonymy, and sinekdok. The figure of speech includes repetition, parallelism, paradoks, anaphora, and polisidentol. 4) Meaning effect includes clearness, force, beauty, and pressing